Corporate communication strategic adaptation for global practice - Goodman, Michael B. 1949-; Hirsch, Peter B. (Peter Lang, 2010)
The chief communication officer at a Fortune 500 multinational corporation today faces the challenges of a rapidly changing global economy, a revolution in communications channels fueled by the Internet, and a substantially transformed understanding of what a 21st-century corporation stands for. This book provides an accessible framework for describing these forces and the specific communication challenges that they have thrown at the global corporation. The text reviews the evolution of society's response to the development of the modern company and the corporate communication practices that grew up in response to it, as well as examining the impact of globalization, Web 2.0 and the networked enterprise on current corporate relationships with key stakeholders such as customers, employees, shareholders, communities and regulators. In examining these forces and how they are interwoven, the authors offer insights and strategies for deploying effective communication as a strategic business asset in today's global economy. Designed for the advanced student of corporate communication, the book contains updated guidelines for the management of investor relations, community relations and other corporate relationships in the age of social media. Specific recommendations for how to organize and execute effective communication for the contemporary practitioner working in the communication field are also provided.